Multiplex Photoluminescent Silicon Nanoprobe for Diagnostic Bioimaging and Intracellular Analysis - Meysam Keshavarz; Bo Tan; Krishnan Venkatakrishnan (Advanced Science, 2018)
Abstract Herein, a label‐free multiplex photoluminescent silicon nanoprobe (PLSN‐probe) is introduced as a potential substitute for quantum dots (QDs) in bioimaging. An inherently non‐photoluminescent silicon substrate is altered to create the PLSN‐probe, to overcome the major drawbacks of presently available QDs. Additionally, crystallinity alterations of the multiplane crystalline PLSN‐probes lead to broad absorption and multiplex fluorescence emissions, which are attributed to the simultaneous existence of multiple crystal planes. The PLSN‐probe not only demonstrates unique optical properties that can be exploited for bioimaging but also exhibits cell‐selective uptake that allows the differentiation and diagnosis of HeLa and fibroblast cells. Moreover, multiplex emissions of the PLSN‐probe illuminate different organelles such as the nucleus, nucleolemma, and cytoskeleton, depending on size‐based preferential uptake by the cell organs. This in vitro study reveals that cancerous HeLa cells have a higher propensity for taking up the PLSN‐probe compared to fibroblast cells, allowing the diagnosis of cancerous HeLa cells. Additionally, the fluorescence intensity per unit area of the cell is found to be a reliable means for distinguishing between dead and healthy cells. It is anticipated that the multifunctionality of the PLSN‐probes will lead to better insight into the use of such probes for bioimaging and diagnosis applications.